2004
DOI: 10.2466/pms.99.7.968-974
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Strategies of Soccer Players in One-on-One Defensive Situations on the Field

Abstract: This study analyzed visual search strategies of soccer players in one-on-one defensive situations on the field. The 8 subjects were 4 experts and 4 novices. While subjects tackled an offensive player for possession of the ball, their eye movements were measured and analyzed. Statistically significant differences between the visual search strategies of experts and novices showed experts fixated more often on both the knee and the hip regions of opponents than novices did. This suggests that information gained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Williams and Elliott (1999) and Milazzo et al (2016b) indicated that expert karate fighters "visually anchored" their attention on the head and torso, while Ripoll et al (1995) showed that expert French boxers maintained foveal fixation mainly on the central regions of their opponent's body as a "visual pivot, " while using their peripheral vision to monitor their opponent's limb movements. Such "visual pivot" or "visual anchor" strategies have been reported in other sports like baseball batting (Kato and Fukuda, 2002), soccer penalty kicking (Savelsbergh et al, 2002;Piras and Vickers, 2011), one-on-one defense in soccer (Nagano et al, 2004), golf putting (Naito et al, 2004), and volleyball reception (Vansteenkiste et al, 2014), which indicates that these strategies are not only confined to combat sports. More recently, Vater et al (2019) proposed the definition and operationalization possibilities of three different gaze strategies: the "foveal spot, " the "gaze anchor, " and the "visual pivot."…”
Section: Discussionmentioning
confidence: 67%
“…Williams and Elliott (1999) and Milazzo et al (2016b) indicated that expert karate fighters "visually anchored" their attention on the head and torso, while Ripoll et al (1995) showed that expert French boxers maintained foveal fixation mainly on the central regions of their opponent's body as a "visual pivot, " while using their peripheral vision to monitor their opponent's limb movements. Such "visual pivot" or "visual anchor" strategies have been reported in other sports like baseball batting (Kato and Fukuda, 2002), soccer penalty kicking (Savelsbergh et al, 2002;Piras and Vickers, 2011), one-on-one defense in soccer (Nagano et al, 2004), golf putting (Naito et al, 2004), and volleyball reception (Vansteenkiste et al, 2014), which indicates that these strategies are not only confined to combat sports. More recently, Vater et al (2019) proposed the definition and operationalization possibilities of three different gaze strategies: the "foveal spot, " the "gaze anchor, " and the "visual pivot."…”
Section: Discussionmentioning
confidence: 67%
“…By foveating the door edges, the participants were better able to ascertain the door's position, while short fixation durations allowed the participants to process each door's location more frequently. The differences in spatio-temporal patterns of fixation while walking or using a wheelchair seem to be similar to those between elite and non-elite athletes [38][39][40][41] in that non-elite participants had shorter fixations and more frequent saccades at critical moments. The clear differences in the spatio-temporal patterns of eye movement indicate that visual information necessary for representing a space in relation to the person-plus-object is different depending on whether the locomotion form is well learned.…”
Section: ) Rapid Adaptation To Altered Bodily States When Using a Famentioning
confidence: 88%
“…1,2 Studies have been completed regarding anticipation in soccer for goalkeepers right before the penalty kick 3,4 and free kick, 5 and for defense when offense approaches. [6][7][8] Results of this research indicate that elite and skilled athletes are better able to anticipate the direction of the ball, the type of ball, and the opponent's movement that are less skilled athletes. Elite baseball batters are better able to anticipate the type and course of a pitch than are less skilled baseball players.…”
Section: Introductionmentioning
confidence: 88%